2004
DOI: 10.1111/j.0020-6598.2004.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pricing of Job Characteristics When Markets Do Not Clear: Theory and Policy Implications*

Abstract: This article examines nonsequential search when jobs vary with respect to nonpecuniary characteristics. In the presence of frictions in the labor market, the equilibrium job distribution need not show evidence of compensating wage differentials. The model also generates several pervasive features of labor markets: unemployment and vacancies, apparent discrimination, and market segmentation. When workers are homogeneous, restrictions on the range of job offers decrease welfare and cannot reduce unemployment. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
60
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 15 publications
8
60
0
Order By: Relevance
“…Although nonwage job characteristics can be included in search models (e.g. Blau 1991;Hwang et al 1998;Lang and Majumdar 2004), this possibility has attracted more attention in the empirical work that is less directly tied to search models.…”
mentioning
confidence: 99%
“…Although nonwage job characteristics can be included in search models (e.g. Blau 1991;Hwang et al 1998;Lang and Majumdar 2004), this possibility has attracted more attention in the empirical work that is less directly tied to search models.…”
mentioning
confidence: 99%
“…The driving factor of our result is the matching pattern of jobs and workers that is determined by their distributions. Hwang et al (1998) and Lang and Majumdar (2004) also find that the observed wage differentials across jobs are not necessarily reflected solely by compensating wage differentials. However, their findings are significantly different from ours in that worker productivity is homogeneous and labour market friction plays the central role in their model.…”
Section: Empirical Implicationsmentioning
confidence: 87%
“…An explanation based on economic theory, rather than econometric theory, is provided by Hwang et al (1998) and Lang and Majumdar (2004). They show that labour market frictions make it less likely to observe compensating wage differentials, using a search model with homogeneous worker productivity.…”
Section: Introductionmentioning
confidence: 99%
“…An explanation based on economic theory, rather than econometric theory, is provided by Hwang et al (1998) and Lang and Majumdar (2004). They show that labor market frictions make it less likely to observe compensating wage differentials, using a search model with homogeneous worker productivity.…”
Section: Introductionmentioning
confidence: 99%